Оцінка компетентності як фактору підвищення конкурентоспроможності персоналу - Романюк, Л. М.; Вдовиченко, Л. В.; Romaniuk, Ludmila; Vdovychenko, Lidiy (КНТУ, 2014)
У статті обґрунтовано вимоги до персоналу залежно від конкурентних стратегій підприємства. Представлено карти компетентності, які є важливим інструментом у системі стратегічного управління персоналом та містять опис усіх вимог до посад та функцій, необхідних для реалізації відповідного виду конкурентної стратегії. Розроблено методику бальної оцінки рівня компетентності керівників усіх ланок та фахівців підприємств, яка дозволяє виявити ступінь відповідності наявного рівня компетентності працівників вимогам тих посад, які вони обіймають. The thesis investigates conceptual approaches for evaluation of personnel competence in order to increase competitive ability of an enterprise. The thesis defines the main requirements for the personnel, depending on competitive strategies of an enterprise. The main components of personnel competence were defined: general and professional knowledge, experience, personal qualities of a worker that can have a positive or a negative influence on the working process. Competence maps for the specialists and managers of machine-building enterprises applicable for various concurrent strategies were presented. Competence maps help to solve the most important problems of personnel policy; to define competence requirements for the managers and specialists; to analyze the compliance of workers to their posts. Competence maps are an important instrument in personnel management strategy system. Rating-based approach based on the competence maps was suggested for evaluation of the competence level of the managers and specialists of all the departments of an enterprise. That allows using the differentiated approach for defying the competence level, will help to optimize the qualitative characteristics, to plan the career, to develop the programs for the job rotation, which would increase the personnel concurrent ability and the concurrence advantages of an enterprise.
Evaluation of personnel competence as a factor of competitive ability
Keywords: стратегія; персонал; компетентність; стратегічне управління; конкурентоспроможність; strategy; personnel; competence; management strategy; competitive ability